Occupational injuries at a Paper Enterprise, Mpumalanga, between 2000 – 2004 - Dlamini, Thembinkosi John (My University, 2008)
Abstract Occupational injury data forms part of the essential information needed for the overall accident prevention strategy for any workplace. It is one of the important tools that is normally used to measure safety performance, as well as to identify the most frequently occurring accidents within a workplace, with the aim of enhancing safety improvement strategies. Lack of accurate information regarding the type, nature and extent of occupational injuries within this Paper Enterprise has resulted in poor prioritisation of safety services. This study was, therefore, aimed at investigating the types and causes of occupational accidents that occurred in a Paper Mill during 2000 - 2004, thus helping the institution to focus its services accordingly. In achieving this, the following objectives were set: · To describe the types, nature and extent or severity of occupational injuries within the Paper Mill, between the years 2000 - 2004; · To identify the most common type of occupational injuries within the Paper Mill, between the years 2000 -2004; and A retrospective review of all occupational injuries that occurred between the years 2000 and 2004, within the Paper Enterprise was carried out. Three hundred and forty one incidents of injury data were recorded from the Mill’s Safety Incident Register and transposed into an occupational Injury Data Sheet, specifically designed for this study. During their transfer the Health and Safety Executive’s method of classifying occupational accidents was used, where injuries were classified according to the type of injury, severity of the injury, part of the body injured and occupation of the employee. ). Injuries were counted per incident irrespective of whether an employee has been injured more than once. In determining the rates the Injury Frequency Rate was used (see definition of terms) which uses the man - hours worked, as denominator value, as opposed to the number of employees. The data was then entered into an Excel spreadsheet, after which it was statistically analysed using Epi - Info. Basic descriptive statistics were used to summarise the data, identifying the most common types of accidents. The most striking points of the study were that wounds (41.6%) and eye injuries (26.7%) were the most frequently occurring injuries, sustained through slipping and falling (18.2%), poor handling practices (13.8%), as well as wind related (24.0%). Of the total, 65.7% was sustained by the enterprise’s own employees, with a Total Incident Rate of 17.0% per 100 employees, which was the highest in all employee categories. Moreover, artisans (38.8%), assistant workers (35.7%), supervisors (22.1%), as well as students and employees with less than one year of employment were the occupations with most injuries. Encouraging, though, was the steady decline in the Total Injury Frequency Rate (TIFR) on yearly basis, from 17.3 in 2000 to 9.2 in 2004. Especially the First Aid Cases (FAC), which accounted for 89.1% of the total. Contrary to these positive results were Medical Treated Cases (MTC), which showed a sharp increase of 18% in 2004, while the number of Lost Time Injuries (LTI) remained constant throughout the study period with an average of 2 cases per year. However, the findings of the study must be considered in light of the fact that the completeness of the incident reporting within the Mill could not be verified. However, the accessibility and ready availability of the clinic facility might have motivated the relatively complete reporting of incidents. Also to be noted is the change in clinical staff, during the period of the study, which might have also had an effect on the consistency of injury assessment, subsequently, affecting the overall classification of injuries within the Mill. The absence of certain denominator data of employees’ i.e. total employees within shift, age and certain employment categories has made the calculation of rates impossible, hence comparing changes were difficult. Besides these possible limitations, this study was able to recommend areas for improvement, especially with regards to equipment and material handling practices, as well as to identify specific incidents associated with slipping and falling. A particular concern that was identified, though, was the high number of injuries sustained by supervisors, reflecting unsatisfactory application of leadership in the areas of safety results, especially with respect to cultural transformation. Therefore, the study recommended a continuous safety awareness and developmental programme for this group (supervisors) including artisans and operators that will address cultural change specifically amongst the new and inexperienced employees, as well as the old and complacent employees within the Mill for the purpose of creating and sustaining an injury free workplace. The study must, however, be regarded as a preliminary evaluation of the causes of injury, as it is based solely on information derived from the incident register, hence the current findings may provide baseline information. Therefore, further investigations should perhaps be done to determine the contribution of specific conditions, behaviours and work practices to injury occurrences.